(untitled) (Archives of Mechanics - Test, 1996)
For periodic, two-dimensional potecntials satisfying the Laplace equation, a new functional basis, different from that used by RAYLEIGH [1], has been derived. This basis allowed us to construct a simple recurrence formulae for evaluation of an effective transport coefficients for regular two-dimensional composites. As an example, the power expansion of an overall conductivity for square array of circular cylinders has been evaluated.